Procedural Political Liberalism and Political Islam - Benhenda, Mostapha (Islamic Studies, 2010)
The conceptual challenge raised by political Islam to liberalism is of a fundamental nature. Political Islam in particular challenges liberalism’s conception of the human person. For political liberalism, persons must be viewed as sovereign. On the contrary, for political Islam, persons are vice-regents of God. In order to overcome this opposition, we restate a famous American political theory, Rawls’s political liberalism, in a purely procedural way. In this restatement, we do not assume the citizens’ agreement on any conception of the person. Instead, we only rely on their commitment to engage in a particular form of dialogue. More precisely, we design an idealized procedure of deliberation between people holding conflicting moral views. We illustrate this procedure with the case of Islamists and liberals. We attempt to show how this procedure can lead the followers of political Islam to endorse liberal political positions and/or vice versa.